Analysis of uncertainties in MEMS and their influence on dynamic properties - Uhl, T.; Martowicz, A.; Codreanu, I.; Klepka, A. (Archives of Mechanics, 2009)
An application of uncertainty analysis of microelectromechanical resonator is presented. A number of different uncertain parameters have been considered, connected both to geometric characteristics and material property. Sensitivity analysis has been carried out in order to study the influence of each input uncertain parameter on the chosen dynamic characteristics. The propagation of given uncertainties into the variation of studied output parameter has been evaluated by means of the Monte Carlo simulation, the vertex method and genetic algorithms. Finite element model of microresonator has been elaborated. It has taken into account the phenomenon of viscous damping coming from the presence of surrounding air as well as the inï¬‚uence of constant electrostatic field.